Cote d'Ivoire : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper and Statistical Appendix examines performance of Cote d'lvoire under the 1994-96 programs. The paper highlights that the government's medium-term adjustment strategy for 1994-96, which was supported by a three-year arrangement under the Enhanced Structural Adjustment Facility, aimed at a rapid restoration of the conditions necessary for sustained economic growth and accelerated progress toward domestic and external financial viability. In addition, the program focused on consolidation of the improved competitiveness of the economy strengthening of public finances and reorientation of public expenditure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet